Pengembangan Sistem Informasi Bank Sampah untuk Optimalisasi Pengelolaan Data - Nuraini, Fina; Sutopo, Joko (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2023)
Bank Sampah Sumber Rejeki in Cilacap City provides an opportunity for customers to deposit waste and receive monetary rewards. Unfortunately, current data management is still manual through unstructured notebooks, potentially resulting in data loss due to notebook damage, difficulty in finding customer information, and delays in making performance reports. This research aims to develop a website-based management information system that is tailored to the needs of the sampah bank. This system includes customer data management, recording waste deposit transactions, recording customer balance withdrawals, and improving waste bank data security. Data was collected through direct interviews with the manager of Sumber Rejeki Waste Bank. The development method used is Feature Driven Development (FDD) using the PHP programming language and MySQL database. In addition, testing this system also involves the black box testing method to ensure the functionality is as expected. The result of this research is a web-based system that is significant in improving the efficiency of managing customer data, transactions, and waste bank performance reports. The implementation of this system reduces the risk of errors and data loss due to manual recording and provides easier access for customers to view transaction history in the waste bank.